RANCANG BANGUN SISTEM PENJERNIHAN AIR OTOMATIS BERDASARKAN TURBIDITYMETER BERBASIS MIKROKONTROLLER - Affan Bachri (Universitas Islam Lamongan, 2018)
The turbidity sensor works by reading the water particles turbidity level captured by the Light Dependent Resistor (LDR) that has been emitted by the laser light. Therefore, the LDR resistance score changes and it makes the Nephelometric Turbidity Units (NTU) score also changes. The solenoid valve is controlled by the suitability of the readings of the desired turbidity meter sensor by the operator.